Politeness in the Samawa Ethnic Language on Social Media - Mahsun Mahsun; Aswandikari Aswandikari; Sukri Sukri; Burhanuddin Burhanuddin; Yatimah Laili Yuparni Durratun; Sari Eva Novita (SHS Web of Conferences, 2024)
This research explains politeness in the Sumbawa ethnic language on social media, including the types of politeness that tend to be used. The politeness theories of Lakoff, Leech, Brown and Levinson, Grice, and Pranowo are the theories used to explain this. Data was collected using documentation methods through the use of language on social media sites such as Instagram, Facebook, and WhatsApp, either individually or in groups. The data was then analyzed using principles in pragmatic studies. The research results show that not all types of language politeness proposed by experts are used by the Sumbawa ethnic group. The politeness type of giving sympathy, showing agreement or similarity, giving praise, and avoiding arguments are the dominant types of politeness used with the person you are talking to. Comprehensive studies need to be carried out in all domains to obtain a politeness model for the Sumbawa ethnic language.